Overview of Early Warning Alert Respone System (EWARS) Performance at Trenggalek District in 2016 - melisa putri anggraini (Universitas Airlangga, 2017)
The implementation of the Early Warning Alert and Response System (EWARS) in Trenggalek District has been implemented since 2013. The accuracy and completeness of reporting is an indicator in determining the performance of Public Health Centers (PHC) in EWARS's implementation. This study aims to analyze the performance of the PHC EWARS at the Trenggalek District Health Office in 2016 by looking at the accuracy and completeness of the reporting. This study was an observational study, using an evaluation design. The research subjects were the EWARS surveillance system in the Trenggalek District Health Office in 2016 and the informants were EWARS holders in 22 health centers and the Health Office. Data collection techniques using primary data and secondary data with instruments in the form of questionnaires and observation sheets. Descriptive data processing and analysis techniques. The results showed the accuracy of reporting in the District of Trenggalek in 2016 obtained an average of 79%, while the completeness of the reporting of the District of Trenggalek in 2016 was 98.5%. The conclusion of the study is the performance of PHC EWARS viewed from the accuracy of reporting. shows poor results because of the accuracy of reporting that has not met the target of 80%, while the completeness of reporting shows that the performance of PHC EWARS is already good because it has met the target of 90%. Accuracy and completeness are influenced by the characteristics of EWARS officers, so there is a need to evaluate officers between the ages of 26-45 years, female officers, and officers who have a working period more than 2 years.